2023
DOI: 10.1093/cid/ciad064
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ocular Candidiasis and Candida Endophthalmitis in Patients With Candidemia: A Systematic Review and Meta-Analysis

Abstract: Background Infectious diseases and ophthalmology professional societies have disagreed regarding ocular screening in patients with candidemia. This study aimed to summarize the current evidence on the prevalence of ocular candidiasis (OC) and Candida endophthalmitis (CE) according to the standardized definitions. Methods A literature search was conducted from the 1990s through October 16th, 2022, using PubMed, Embase, and SCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Although a recent systematic review suggested that universal ophthalmological examination does not improve outcomes [37], the Infectious Diseases Society of America (IDSA) and the European Confederation of Medical Mycology (ECMM) guidelines both recommend that all patients with candidemia should undergo routine dilated funduscopic exam [19,38]. These recommendations were supported by a recent meta-analysis by Phongkhun et al, which found that ocular manifestations in patients with candidemia were more common than previously reported by the American Academy of Ophthalmology (AAO), which suggested an incidence of less than 0.9% [39]. These discrepancies emphasize that further studies are needed to identify high-risk patients that would benefit the most from this intervention.…”
Section: Discussionmentioning
confidence: 96%
“…Although a recent systematic review suggested that universal ophthalmological examination does not improve outcomes [37], the Infectious Diseases Society of America (IDSA) and the European Confederation of Medical Mycology (ECMM) guidelines both recommend that all patients with candidemia should undergo routine dilated funduscopic exam [19,38]. These recommendations were supported by a recent meta-analysis by Phongkhun et al, which found that ocular manifestations in patients with candidemia were more common than previously reported by the American Academy of Ophthalmology (AAO), which suggested an incidence of less than 0.9% [39]. These discrepancies emphasize that further studies are needed to identify high-risk patients that would benefit the most from this intervention.…”
Section: Discussionmentioning
confidence: 96%
“… 76 These criteria based on recent data, reviews, and statements by the Royal College of Ophthalmologists and the American Academy of Ophthalmology have not yet been evaluated by the IDSA. 77 78 Patients with ocular involvement should have an infectious disease consultation.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of fungemia by W. anomalus most commonly included fever and sepsis, while no patient was diagnosed with endophthalmitis in the studies evaluated in the present review. Notably, in candidemia, the rate of endophthalmitis was identified in a recent systematic review to be between 1% and 4%, depending on the geographic region where candidemia occurred [ 78 ]. The patients in the current review are relatively few, and more data are required to draw safe conclusions; however, it could be that this fungus does not have a significant tendency to cause endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%